How moral codes evolve in a trust game - Jean Paul Rabanal; Daniel Friedman (Games, 2015)
This paper analyzes the dynamic stability of moral codes in a two population trust game. Guided by a moral code, members of one population, the Trustors, are willing to punish members of the other population, the Trustees, who defect. Under replicator dynamics, adherence to the moral code has unstable oscillations around an interior Nash Equilibrium (NE), but under smoothed best response dynamics we obtain convergence to Quantal Response Equilibrium (QRE).
Keywords: C72; C73; 330; Prisoner's Dilemma; evolutionary stability; moral codes